PEMANFAATAN LEMBAR KERJA SISWA DALAM PENINGKATAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM: STUDI KASUS DI SMP DARUL MAARIF SAMPANG - Muhammad Yusron Maulana El-Yunusi; Mansur Mansur; Asrori Mahmud; Samsul Hadi (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2023)
The study discusses the use of Student Worksheet (Lembar Kerja Siswa) in Islamic Religious Education (Pendidikan Agama Islam) subject in SMP Darul Maarif. Student Worksheet is a tool that helps to activate students in learning and improve communication in the classroom. Student Worksheet contains instructions and guidance that assist students in completing their tasks by covering the basic competencies that need to be achieved. Student Worksheet has different functions for teachers and students, where Student Worksheet makes it easier for students to understand the subject matter, while for teachers, Student Worksheet serves as a guide in directing students and considering the thought process that needs to be developed in students. This study aims to determine the process, interest, and influence of Student Worksheet utilization in Islamic Religious Education subject. The research methodology uses a qualitative approach with descriptive research. The data collection techniques are a questionnaire, observation, interview, and documentation. The results show that Student Worksheet helps students understand the subject matter, saves time, and serves as an evaluation tool. The use of Student Worksheet in Islamic Religious Education subject in SMP Darul Maarif is still not maximized; therefore, this study is conducted to optimize its usage. The study concludes that Student Worksheet can improve students' interest and understanding of the subject matter, and teachers need to develop teaching materials that are attractive and easily understood by students, especially in the field of Islamic Religious Education subject.